BEYOND TOLERANCE AND MODERATION: FRIENDSHIP AS RELATIONAL EPISTEMOLOGY FOR PUBLIC THEOLOGY IN PLURAL INDONESIA - Lucky Paulus Tumbelaka; Ineke Marlien Tombeng; Linda Patricia Ratag; Mieke Nova Sendow; Maria Elisa Tulangouw (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This paper reinvents the idea of public theology within the Indonesian context by developing friendship as a relational, epistemic, and praxis-based category instead of defining public theology as institutional speech, commentary of policy, or moral intervention. The research begins at a threefold distance. To begin with, influential public theology scholarship has eloquently elucidated the public work of theology, but has favored discourse, civil society, and institutional ethics to thick descriptions of interpersonal relationality. Second, the recent discussions in Indonesia have fruitfully engaged friendship as a leading grammar of public theological engagement across religious difference but have failed to develop friendship as a leading grammar of nationalism, polarization, religious moderation, and contextual theology. Third, the readings of John 4 have frequently been focused on mission, gender or interfaith dialogue, but have seldom been incorporated into a constructive model of public theology in plural societies. The article has a qualitative, constructive theological design, which implies the combination of literature-based analysis of the key debates in the field of public theology and contextual theology with the contextual hermeneutical analysis of the text of John 4:5-26, with reference to John 4:42 where necessary. This article posits that friendship must be conceptualized in three interrelated ways, as relational epistemology, that friendship imparts humility, reciprocity and solidarity; and as public praxis, that friendship establishes joint spaces and collaborative working areas without obliterating theological difference. It is argued that an effective Indonesian public theology should transcend a thin politics of tolerance to a thicker form of friendship that is dialogical, cross-boundary and publicly accountable. By doing this, the article adds to the transferable framework of global public theology in plural societies but is still grounded in Indonesian realities.